2021
DOI: 10.1108/bfj-11-2020-1059
|View full text |Cite
|
Sign up to set email alerts
|

How can consumer involvement be changed through communication campaigns? An information content choice model applied to the olive oil case

Abstract: PurposeInvolvement has been one of the most studied variables in the field of marketing due to its determinant role in consumer behaviour, but always as a contextual or mediating variable. Taking its relationship with knowledge as the starting point, in this work, the purpose of this paper is to examine how to use the choice of information content in communication campaigns to drive up the level of involvement. A new method based on Qualitative Comparative Analysis (QCA) models is applied to the case of olive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 84 publications
(131 reference statements)
0
3
0
Order By: Relevance
“…Malaysian e-consumers were found to be triggered by their personal involvement with fashion products, which impacts how they perceive the product quality and response through their decision to buy/not-to buy the product. Results could be understood within the concept of product knowledge which led consumers into being involved with the product/brand/retailer (Elsharnouby et al, 2021;Garrido-Castro et al, 2021). Earlier study by Bhaduri and Stanforth (2017) confirmed product descriptions affecting high involved luxury fashion consumers and influencing their perceived value.…”
Section: Key Findingsmentioning
confidence: 88%
See 1 more Smart Citation
“…Malaysian e-consumers were found to be triggered by their personal involvement with fashion products, which impacts how they perceive the product quality and response through their decision to buy/not-to buy the product. Results could be understood within the concept of product knowledge which led consumers into being involved with the product/brand/retailer (Elsharnouby et al, 2021;Garrido-Castro et al, 2021). Earlier study by Bhaduri and Stanforth (2017) confirmed product descriptions affecting high involved luxury fashion consumers and influencing their perceived value.…”
Section: Key Findingsmentioning
confidence: 88%
“…Results could be understood within the concept of product knowledge which led consumers into being involved with the product/brand/retailer (Elsharnouby et al. , 2021; Garrido-Castro et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, details of the methods used in the five case studies (experimental design, questionnaires, etc.) can be found in the following references(Garrido-Castro and Torres-Ruiz, 2019;Garrido-Castro et al, 2021;Gutierrez-Salcedo et al, 2021;Marano-Marcolini and Torres-Ruiz, 2017)…”
mentioning
confidence: 99%